The Effect of Animal Bone Ash on the Mechanical Properties of Asphalt Concrete - Yasir N. Kadhim; Wail Asim Mohammad Hussain; Abdulrasool Thamer Abdulrasool (Civil Engineering Journal, 2021)
For the sake of enhancing the mechanical properties and durability of asphalt concrete, many studies suggest adding different admixtures, such as waste materials in the form of filler. These admixtures have a significant influence on the performance of asphalt concrete by plying a roll in filling the voids between particles and sometimes as a cementitious material. This study aims to improve the strength of asphalt concrete by adding crushed animal bone to the mix after carbonization at a temperature of 800 Co. Seven different percentages (10, 20, 30, 40, 50, 60, and 100%) of animal bone ash as a replacement for the filler percentage were added to the optimum asphalt concrete mix. A number of tests were conducted on asphalt concrete specimens to measure Marshall stability (MS), Marshall flow value (MF), voids filled with asphalt percentages (VFA), air void percentages (VA), voids in mineral aggregate percentages (VMA), and maximum theoretical specific gravity (GMM). From the results, the maximum stability of 14.85 KN was reached when using animal bone ash of 20% as a partial replacement for the conventionally used filler (limestone). In general, there are some improvements in the physical properties of asphalt concrete with animal bone ash, which can be related to the increase in the bond between the particles of aggregates and the bitumen material. Doi: 10.28991/cej-2021-03091757 Full Text: PDF